Rapid in situ formation and densification of titanium boride (TiB) nano-ceramic via transient liquid phase in electric field activated sintering. (October 2016) - Du, J.; Sanders, A.P.; Jindal, V.; Chandran, K.S. Ravi
Abstract: Rapid in situ synthesis of bulk nanostructured titanium boride (TiB) ceramic, at the lowest possible processing temperature, is demonstrated. Using electric-field-activated-sintering (EFAS), nanoscale TiB whiskers were formed and densified uniformly throughout the volume, from a mixture of micron-sized Ti, TiB2 and FeMo powders, at 1100 °C in 30 min and at a relatively low pressure. Microstructure and X-ray diffraction (XRD) analysis, revealing the formation of TiB whiskers in this rapid processing condition, are presented. The formation of a transitional quaternary liquid phase, facilitated by localized joule heating at particle contacts, are hypothesized as contributors to rapid and low-temperature synthesis. Graphical abstract: